Applying for RAMP Using a Cohort Model: Results of a Multilevel Case Study. Issue 1 (21st February 2022) - Goodman-Scott, Emily C.; Taylor, Julia V.; Walsh, Robyn
School counselors across the United States are implementing comprehensive school counseling programs, such as those following the American School Counselor Association (ASCA) National Model. ASCA awards a designation honoring exemplary school counseling programs: Recognized ASCA Model Program (RAMP). Although a growing number of studies have examined RAMP status through survey methods and student outcomes, the need remains to understand RAMP through the lens of each school's unique context and experience. We present a multilevel, qualitative, participatory, descriptive case study to examine a school counseling cohort preparing over a 2-year period to apply for RAMP, utilizing a district–university partnership. Given the expansive data gleaned from the present study, the results are reported in two articles; this is the first of a two-part study. Results highlight this RAMP cohort process, including the following themes: (a) the push and pull of deciding to participate, (b) collaborative supports, (c) facilitators' integral and complex role, and (d) next steps.